Fluorine-rich calcic amphiboles in ultrahigh-temperature mafic granulite from Tonagh Island in the Napier Complex, East Antarctica: Preliminary report - Tsunogae, Toshiaki; Osanai, Yasuhito; Toyoshima, Tsuyoshi; Owada, Masaaki; Hokada, Tomokazu; Crowe, Warwick A. (National Institute of Polar Research, 2000)
P(論文) Fluorine-rich calcic amphiboles occur in ultrahigh-temperature mafic granulite from Tonagh Island in the Napier Complex, East Antarctica The amphiboles are subdivided into two types high-grade brownish to pale brownish amphibole and retrograde greenish amphibole The brownish amphibole is pargasitic occurring as a subhedral grain in two-pyroxene mafic granulite It contains up to 2 2 wt% fluorine, which corresponds to an F/(F + Cl + OH) ratio of 0 54 (sample B98020801) In sample B98020802B, brownish amphibole is rimmed by an orthopyroxene-plagioclase-quartz corona, probably formed by a devolatilization reaction It has a lower fluorine content of 0 21-0 52 wt% (F/(F +Cl + OH) = 004-0 13) Pale brownish amphibole is a minor phase in metapyroxenite It has the highest fluorine content (2 6 wt%, F/(F + C1 + OH) = 0 60, sample B98012802F) Greenish amphibole is present as fine-grained aggregates with quartz, rimming ortho- and clinopyroxenes Fluorine is almost absent in this amphibole Holloway and Ford (1975) experimentally determined that pargasite with a F/(F +Cl + OH) ratio of 0 48 is stable up to 1100℃ at 5 kbar, and that F/(F + C1 + OH) increases with increasing temperature The fluorine-rich calcic amphiboles in mafic granulites are therefore stable under UHT metamorphic conditions The formation of an orthopyroxene-plagioclase-quartz corona in sample B98020802B can therefore be explained by breakdown of the amphibole due to its low-fluorine content The origin of the fluorine is not known, but it is probably derived from basic magma at the stage of protolith formation departmental bulletin paper